FAKTOR-FAKTOR YANG MEMPENGARUHI PENYERAPAN TENAGA KERJA PADA UMKM KERAJINAN ANYAMAN BAMBU DI KABUPATEN LOMBOK UTARA - Lestari, Eke Febi; Satarudin, Satarudin; Sujadi, Sujadi (Jurnal Konstanta, 2025)
This research aims to determine the impact of capital, wages, and sales turnover on labor absorption in Micro, Small, and Medium Enterprises engaged in bamboo weaving crafts in North Lombok Regency. This research was conducted in North Lombok Regency because it is an area with potential for developing bamboo weaving crafts, with several micro, small, and medium enterprises serving as platforms for bamboo weaving artisans. The analysis used in this research is multiple linear regression analysis. The results and discussion show that partially, the capital variable has a positive and significant effect on labor absorption. Meanwhile, the wage and sales turnover variables have a positive but not significant effect on labor absorption in small and medium enterprises of bamboo weaving crafts in North Lombok Regency.